A NARATIVE INQUIRY INTO TEACHING EXPERIENCES: CHALLENGES TEACHING STRATEGY IN NARATHIWAT THAILAND - Firdausyiah, Aulia; Islam, Syaiful (Universitas Muhammadiyah Metro, 2024)
This study aims to discover the experiences of 2 English teachers regarding challenges and how to deal with them who do not have a background in English education at Witthayathan Islamic School. The method used was narrative inquiry with qualitative research method. Data were obtained through structured interviews with two participant teachers. The results of the analysis showed two themes in the stories told by the two teachers, namely the challenges of teachers when teaching in Thailand, such as teachers who are not English graduates, differences in language structure, and lack of student motivation when learning, as well as teachers' strategies in teaching English by using varied methods such as memorizing ten vocabulary, playing games, reading and speaking exercises to improve students' abilities.